Enterprise architecture as an approach to the development of information systems - Majstorović, Milosav N.; Terzić, Rajko M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The link between business and information technology (IT) has been a constant topic in both academic and industrial circles for more than 30 years. Alignment (compliance) between business and IT is generally seen as an important component and a basis for optimizing the performance of any organization. Due to constant changes in the IT world as well as in modern business, the work on the alignment of business and IT is gaining in importance. The cause of the alignment problem lies primarily in different levels of business abstraction and IT concepts. In order to solve this problem, for a long time, the current approach to the development of information systems (IS) is based on the so-called enterprise architecture (EA). In this paper, a review of literature dealing with EA is given. The focus of the literature review was the identification of works dealing with motivational aspects for the use of EA as well as those that deal more closely with the process of development of EA using general and domain specific frameworks. The aim was also to give an insight into the current picture of academic research in this field and the use of EA in order to solve the problems of business and IT alignment. This overview can be a starting point for participants in EA development using existing frameworks as well as for developing specific frameworks that would be applied in specific domains.